PERCEPTIONS OF MUHAMMADIYAH AND NAHDLATUL ULAMA FIGURES ON CHILDFREE DECISIONS FOR YOUNG COUPLES IN WATES DISTRICT, KEDIRI REGENCY - Irma Nur Afifah; Thoat Stiawan; Salman Al Farisi (Universitas Islam Negeri Mataram, 2023)
Childfree is a decision taken by married couples not to have children. The decision was taken consciously by mutual consent. It is also related to the current trend among young couples not to have children because they feel reluctant to be responsible for their children’s lives and focus on household life as a childless married couple. Apparently, this has also been accepted and validated by several young couples in Wates District, Kediri Regency. Of course, regarding Childfree itself, there is no Islamic law that regulates it, so, in this case, the author uses the perceptions of Muhammadiyah and Nahdlatul Ulama figures to give their views on the Childfree phenomenon among young couples in Wates District, Kediri Regency. This research uses a qualitative approach with descriptive methods. Data collection by interviews and observations of Nahdlatul Ulama and Muhammadiyah figures in Wates District, Kediri Regency. The results of this study indicate that there are various viewpoints regarding childfree, but what has become the agreement of NU and Muhammadiyah figures in Wates District, Kediri Regency, regarding Childfree is that they tend to disagree and encourage young couples to return to their religious knowledge, and to take a holistic approach regarding making that decision. Childfree actions should not be used as a benchmark or a guide in building a household that is sakinah, mawaddah, and rahmah because these actions injure the nature of marriage.